181k views
2 votes
Help me solve this problem please

Help me solve this problem please-example-1
User Osotorrio
by
5.3k points

2 Answers

3 votes

Answer:

C. 16

Explanation:

y^2-z^2

(-5)^2-(-3)^2

25-9

16

User Tardis
by
4.9k points
2 votes

Answer:

Explanation:

y = - 5

y^2 = (-5)^2

y^2 = 25

z = - 3

z^2 = (-3)^2

z^2 = 9

y^2 - z^2 = 25 - 9 = 16

User Younes Belouche
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.